PERENCANAAN KEBUTUHAN PRODUK GUNA OPTIMALISASI WASTE DAN LABA DENGAN APLIKASI FUZZY MULTIOBJECTIVE OPTIMIZATION - Asih, Endang Widuri; Najah, Arini (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
Xx is a company engaged in spinning yarn. This company produces various types of yarns including cotton, rayon, polyester-rayon and polyester-cotton. The problem that often arises at the moment is about optimization of raw materials. During the production process takes, the processing produces waste. This is resulting in unneces-sary costs, thus difficult to achieve optimal benefit. To generate the maximum profit and minimal waste, the company must determine the combination of products and allocate resources optimally. Simak Baca secara fonetik Kamus - Lihat kamus yang lebih detail Terjemahkan situs web mana pun USA Today-Amerika Serikat Museo del Prado-Spanyol OneIndia-Hindi Focus Online-Jerman Vogue-Prancis Marmiton.org-Prancis Machu Picchu-Spanyol NouvelObs-Prancis Nord-Cinema-Prancis Louvre-Prancis Berlingske.dk-Denmark Elle-Prancis Lakukan banyak hal dengan Google Terjemahan Cari resep sushi terbaik di dunia, tentunya dalam bahasa Jepang! Bebaskan kekuatan Penelusuran yang Diterjemahkan Google. Apa sih artinya? Pasang Google Toolbar supaya Anda tidak perlu kesulitan lagi dengan kosakata bahasa asing. Bangun bisnis global Anda. Iklankan ke berbagai bahasa menggunakan Google Peluang Pasar Global. Buku bahasa dalam kantong Anda! Pasang aplikasi Android kami sebelum perjalanan Anda ke Rio. Fuzzy multiobjective optimization is a method for optimized several objective functions bend to several constraints. This method is also application of fuzzy logic for helping company to solve the problems of limited resourse. By analyzing calculation result of linear programming than continued result enter in to fuzzy multi-objective method so to getted optimum product combination base on tolerance of company hoped. Result of research base on fuzzy multiobjective optimization method have got product combination they are rayon 40/1 1601,299 cone with profit Rp. 18170740,4 and waste 118,49 kg. By applying fuzzy multi-objective optimization can reduce waste 8,68 kg.